Respuesta :

Answer:

x=-6

Step-by-step explanation:

[tex]-6+5(1-x)=-13-7x[/tex]

1) Using the distributive property distribute the 5 to the equation in the parenthesis

[tex]-6+5-5x=-13-7x[/tex]

2) Combine the -6 and 5

[tex]-1-5x=-13-7x[/tex]

3) Add 1 to both sides.

[tex]-1(+1)-5x=-13(+1)-7x[/tex]

[tex]-5x=-12-7x[/tex]

4) Add 7x to both sides

[tex]-5x(+7x)=-12-7x(+7x)\\ 2x=-12[/tex]

5) Divide both sides by 2 to isolate the x.

[tex]\frac{2x}{2} =\frac{-12}{2}\\ x=-6[/tex]

sorry this so sloppy, hope this helps!!
Ver imagen ariyanna29
ACCESS MORE